A fast input vector control approach for sub-threshold leakage current reduction at nanoscale transistors. (2015) - Rjoub, Abdoul; Ajlouni, Motasem; Manasrah, Hassan
This paper presents an efficient algorithm to control and reduce the sub-threshold leakage current at nanoscale transistor level. The proposed algorithm called fast input vector algorithm (FIVA) is based on input vector control (IVC) technique. Simulation results showed that the proposed algorithm is faster than other algorithms implemented using the same technique. The speed of the algorithm increases by increasing the number of transistors comparing with other algorithms having the same target, as well as by increasing the number of input vectors in the circuit. The proposed algorithm showed it is capable to save more power dissipation than other algorithms by reducing and controlling the sub-threshold leakage current when the transistor is in the off state. These results and other comparison results in the rest of the paper validate the efficiency of the proposed algorithm.